2013
DOI: 10.1016/j.cct.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Midwest Exercise Trial for the Prevention of Weight Regain: MET POWeR

Abstract: Weight reduction in overweight and obese individual’s results in physiological and behavioral changes that make the prevention of weight regain more difficult than either initial weight loss or the prevention of weight gain. Exercise is recommended for the prevention of weight regain by both governmental agencies and professional organizations. To date, the effectiveness of exercise recommendations for the prevention of weight regain has not been evaluated in a properly designed, adequately powered trial. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A detailed description of the rationale and design for (MET‐POWeR) has been published (19). Adults with overweight or obesity ( n = 298) initiated a 3‐month behavioral WL intervention (−3 to 0 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the rationale and design for (MET‐POWeR) has been published (19). Adults with overweight or obesity ( n = 298) initiated a 3‐month behavioral WL intervention (−3 to 0 months).…”
Section: Methodsmentioning
confidence: 99%
“…The power and sample size were discussed in detail in our previously published rationale and design paper (19). Briefly, sample size estimates were based on an expected weight change (0‐12 months) of 8 kg, 5 kg, and 2 kg with a common SD of 6 kg and a type 1 error rate of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Although cardiovascular risk associated with adiposity can be mitigated by weight loss, the impact is rarely sustainable. Short term weight loss can be achieved with caloric restriction and lifestyle modifications, but approximately half of patients who achieve weight loss will regain up to 75% of the lost weight following 12–30 months of treatment completion [Donnelly et al 2013]. It is unknown how weight regain impacts the androgenic profile, a critical marker of metabolic dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another major component in prevention is body weigh optimization. However, numerous studies involving restricted energy intake and increased physical activity have demonstrated only a short-term effect (not beyond 6 months and mere 5% body weight reduction (18).…”
Section: Discussionmentioning
confidence: 99%